Sustainable Use of Plants for Heavy Metal Removal from Water: Phytoremediation - Bhat, Akash Pundalik; Bhat, Pooja Pundalik (International Journal of Applied Sciences and Biotechnology, 2016)
There are various methods for removal of heavy metals from contaminated water and many of them can be costly and also consume a lot of resources. Phytoremediation is the use of plants as a filter for removal of unwanted elements and substances from contaminated water. This process is called rhizofiltration. Phytoremediation has not achieved a lot of importance on large scale level. This review- study shows how several species like Brassica juncea and Chenopodium amaranticolor, Pistia stratiotes, Helianthus annuus L. and Phaseolus vulgaris L. var. vulgaris, Eleocharis acicularis, Lemna minor L., Phragmites australis and Eichhornia Crassipes can be used for effective removal of heavy metals. These species are selected based on a review on various studies on rhizofiltration. Hence rhizofiltration can be an eco-friendly and innovative method of removal of heavy metals and has to be applied for large scale treatment of heavy metals in real time waters. Int J Appl Sci Biotechnol, Vol 4(2): 150-154